A novel directional pilot protection method for VSC-MTDC based on the initial forward and backward travelling wave head. (July 2019) - Jiang, Lingtong; Chen, Qing; Huang, Wudi; Zeng, Yu; Wang, Lei; Zhao, Pu
Highlights: A phase-mode transform method is used to decouple the bipolar DC cable. The characteristic of the mode currents through the cable is analyzed. A novel directional pilot protection for VSC-MTDC cable based on á trous algorithm is proposed. A four-terminal VSC-MTDC system is built in PSCAD, and the protection method is verified through various simulations. Abstract: This paper proposes a novel directional pilot protection for VSC-MTDC frequency-varying cable lines. Based on a new phase-mode transformation to decouple the bipolar DC cable, this paper utilizes the propagation time difference between 6-th mode forward and backward travelling wave to judge the faulty line and the polarity of 5-th mode current travelling wave to identify the faulty pole. Analysis of the reflection characteristics of the fault travelling wave at the cable terminal shows that (i) when an internal fault occurs, the protection device will detect the arrival of the forward and backward travelling wave simultaneously and (ii) when an external fault occurs, the arrival time difference between the forward and backward travelling wave is a nonzero value. A two-level voltage source converter based four-terminal DC system is modeled in PSCAD, and various faults are simulated to verify the proposed method. Numerous simulation results have indicated that the protection method is robust against noise, and has been tested successfully for fault resistance of up to 400 Ω. In addition, the algorithm has clear setting principles, lower sampling frequency, smaller calculation amount and faster operating speed. Only state signal is sent to the other side, so low communication speed can meet the requirement of relay protection and does not need the data synchronization seriously.